Chemical profile, antioxidant, antimicrobial, enzyme inhibitory, and cytotoxicity of seven Apiaceae species from Turkey: a comparative study - Zengin, Gokhan (2021)
Several Apiaceae species, used as both food and in complementary and alternative medicine, represents a rich source of potential valuable phytopharmaceuticals which necessitates scientific contemplation. In the present study, the antioxidant, enzyme inhibitory, antimicrobial, and cytotoxic properties of methanol extracts of seven Apiaceae species, (Chaerophyllum macrospermum (Willd. ex Spreng.) Fisch. & C.A.Mey. ex Hohen, Ferula rigidula Fisch. ex DC., Ferula orientalis L., Prangos ferulacea Lindl., Prangos peucedanifolia Fenzl., Ferulago setifolia K. Koch, and Pimpinella anthriscoides Boiss.) were evaluated. Species belonging to the Prangos genus exhibited the highest total phenolic content, namely P. peucedanifolia and P. ferulacea, with values of 47.90 and 44.44 mg gallic acid equivalent/g extract, respectively. P. peucedanifolia also displayed the highest radical scavenging capacity (81.53 and 102.70 mg Trolox equivalent [TE]/g extract for 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS), respectively) and reducing power (165.87 and 100.09 mg TE/g extract for cupric reducing antioxidant capacity (CUPRAC) and ferric reducing antioxidant power (FRAP), respectively). C. macrospermum showed the most potent inhibition against Alzheimer's disease related enzymes, namely acetylcholinesterase (4.53 mg galantamine equivalent [GALAE]/g extract) and butyrylcholinesterase (3.22 mg GALAE/g extract). P. ferulacea (131.94 mg kojic acid (KAE) equivalent/g extract) and P. peucedanifolia (4.97 mmol acarbose equivalent (ACAE)/g extract) were potent inhibitors of tyrosinase and a-glucosidase, respectively. In general, studied species were able to reduce cellular viabilities. P. peucedanifolia possessed promising antibacterial potential against Bacillus cereus (Minimum inhibition concentration (MIC): 0.37 mg/mL), L. monocytogenes (MIC: 0.56 mg/mL), P. aeruginosa and Escherichia coli (MIC: 0.27 mg/mL), Salmonella typhimurium and Enterobacter cloacae (MIC: 0.75 mg/mL). F. rigidula showed the highest antifungal effect against Aspergillus ochraceus and Trichoderma viride (MIC: 0.10 mg/mL). The present findings could be the scientific starting point towards the pharmaceutical and/or commercial utilization of these Apiaceae species.